The Relevance of the Kulliyyatul Mu’allimin Al-Islamiyyah (KMI) Curriculum to the Implementation of the Merdeka Curriculum in Modern Islamic Boarding Schools - Rahmatul Husniah; Putri Desi Natalia; Siti Asisah; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aims to analyze the relevance of the Kulliyyatul Mu’allimin al-Islamiyyah (KMI) Curriculum to the implementation of the Merdeka Curriculum in modern pesantren. The study is motivated by the transformation of national educational policy through the Merdeka Curriculum, which emphasizes learning flexibility, character development, and the enhancement of students’ competencies, while modern pesantren have long implemented the KMI educational system oriented toward character formation and holistic education. This study employed a qualitative approach using a library research design. The data sources were obtained from books, scientific journals, academic articles, official documents, and previous studies relevant to the KMI Curriculum, the Merdeka Curriculum, and modern pesantren education. Data collection techniques were conducted through documentation studies, while data analysis employed the content analysis method by critically and systematically examining various literature sources. The findings reveal that the KMI Curriculum possesses strong relevance to the implementation of the Merdeka Curriculum, particularly in the aspects of character development, the cultivation of independence, the reinforcement of religious values, and the holistic development of students’ competencies. Furthermore, the educational values embedded within the KMI system are aligned with the strengthening of the Pancasila Student Profile and twenty-first-century learning promoted by the Merdeka Curriculum. Nevertheless, the integration of both curricula still encounters challenges related to curriculum adjustment, educators’ readiness, and learning management within modern pesantren. Therefore, systematic integration strategies are required to ensure that the implementation of the Merdeka Curriculum in modern pesantren can be carried out effectively without diminishing the identity and values of Islamic education.